Design validation of the moodle-based mobile learning model in higher education - I Lestari; G Yarmi (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
The rapid technical developments bring changes in the field of learning. The impact on technological development that is utilized as instructional media such as mobile learning (M-Learning). The purpose of this study is to produce an M-Learning based on Moodle that has passed the stage of expert validation. This study is part of a large study that lasted about three years. In the first year, research is limited to only the eighth stage of the Dick and Carey instructional design model, which is a formative evaluation for expert validation. Expert validation involved is material experts, media experts, and design learning experts. The technique of collecting data using questioner with data analysis done by the simple descriptive statistic. The subjects from the study are the students of Program Studi Pendidikan Guru Sekolah Dasar, Fakultas Ilmu Pendidikan, Universitas Negeri Jakarta. The results of research on the form of products that have been through the validation stage of experts and ready to be tested on the subject of research to be conducted in the second year of research. This research has implications of the discovery of a conceptual model of Moodle-based M-Learning design for learning in universities.